Association of Helicobacter Pylori Infection and Serum Albumin in Patients on Hemodialysis (Iranian Journal of Kidney Diseases, 2010)
Introduction. Helicobacter pylori infection in gastric mucosa may cause systemic inflammatory reaction. We investigated the inflammatory effect of H pylori infection on nutritional factors such as serum albumin in hemodialysis patients and influence of eradication of H pylori on this association.Materials and Methods. Ninety-eight patients on hemodialysis were divided into 2 groups according to H pylori infection. Eradication of H pylori, 8 weeks after treatment, was confirmed by urease breath test and H pylori stool antigen. Serum albumin, lipid profile, and metabolite levels were checked before and after 8 weeks and 6 months of eradication of H pylori.Results. Thirty-nine patients (39.8%) were infected with H pylori. There were no significant differences between the two groups in age, dialysis duration, serum albumin, serum creatinine, blood urea nitrogen, hemoglobin, serum calcium, serum phosphorus, and lipid profile. Thirty-seven patients with H pylori completed the treatment period. Eradication was successful in 30 patients (81.1%). Eight weeks and 6 months after anti-H pylori drug therapy, the mean serum albumin level significantly decreased from 4.2 mg/dL to 3.6 mg/dL (P < .001) and 3.7 mg/dL (P < .001), respectively. Significant decreases were seen in serum cholesterol (P = .001), blood urea nitrogen (P = .005), and serum calcium level (P = .03) and a significant increase in hemoglobin level (P = .02).Conclusions. Our study did not demonstrate nutritional benefits after H pylori eradication treatment, as the level of nutritional markers reduced. This relationship needs to be confirmed by further prospective studies.